THE ROLE OF GENERAL EDMUND TACZANOWSKI IN CREATING POLAND'S NATIONAL SECURITY - Giebułtowska Magdalena (2021)
The person of General Edmund Taczanowski is not widely known and quoted in the bibliography of the subject. He didn’t have a direct impact on the fate of the Polish state. However, his person played an important role in the course of the Greater Poland Uprising 1918-1919 and the January Uprising. During January Uprising his deeds went down in Polish history. And even though the Uprising fell, the activity of General Edmund Taczanowski testifies to his patriotic attitude and the will to fight for the Polish state. The goal of this article is an attempt to evaluate the actions taken by Edmund Taczanowski for the Polish state. In the first place, define what heroic deeds were his participation and then evaluate them. This assessment should state how Edmund Taczanowski's activity contributed to the creation of national security of the state. The analysis of the heroic deeds of General Edmund Taczanowski testifies to the fact that he contributed to the creation of Poland's national security. An analysis of the heroic deeds of General Edmund Taczanowski demonstrates that he contributed to the creation of Poland's national security.